Circumstantial Indirectness: Future Orientation of Modals Revised - Majdič, Jakob (Proceedings of the Amsterdam Colloquium, 2024)
Circumstantially interpreted modals are obligatorily future oriented. Standard accounts of this correlation rely on a condition demanding that the modal base must be diverse with respect to the prejacent proposition (e.g. Condoravdi 2002; Rullmann and Matthewson 2018; Williamson 2021). I present evidence against this account by showing that circumstantial will is veridical and compatible with full certainty of the prejacent. I develop an account on which future orientation of circumstantial modals results from an ‘indirectness presupposition’ that has been independently motivated for the epistemic domain (von Fintel and Gillies 2010).